2018
DOI: 10.3996/102017-jfwm-084
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vital Rates for the Hawaiian Gallinule, a Cryptic, Endangered Waterbird

Abstract: Vital rates describe the demographic traits of organisms and are an essential resource for wildlife managers to assess local resource conditions and to set objectives for and evaluate management actions. Endangered waterbirds on the Hawaiian Islands have been managed intensively at state and federal refuges since the 1970s, but with little quantitative research on their life history. Information on the vital rates of these taxa is needed to assess the efficacy of different management strategies and to target p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Rallidae species have colonized oceanic islands all over the world, but are reluctant fliers when not dispersing (Ripley et al., 1977). Although genetic (Miller, Mullins, Haig, Takano, & Garcia, 2015) and observational (Takano & Haig, 2004; Worthington, 1998) evidence of long‐distance (~120 km) movements over open ocean water exist for the Marianas common moorhen, no movements of Hawaiian gallinules have been observed between the two islands they inhabit (Kaua`i and O`ahu, ~138 km apart), despite extensive mark–recapture efforts (Dibben‐Young, 2010; van Rees et al., 2018). There is accordingly some uncertainty with regard to the willingness of Hawaiian gallinules to disperse over open ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Rallidae species have colonized oceanic islands all over the world, but are reluctant fliers when not dispersing (Ripley et al., 1977). Although genetic (Miller, Mullins, Haig, Takano, & Garcia, 2015) and observational (Takano & Haig, 2004; Worthington, 1998) evidence of long‐distance (~120 km) movements over open ocean water exist for the Marianas common moorhen, no movements of Hawaiian gallinules have been observed between the two islands they inhabit (Kaua`i and O`ahu, ~138 km apart), despite extensive mark–recapture efforts (Dibben‐Young, 2010; van Rees et al., 2018). There is accordingly some uncertainty with regard to the willingness of Hawaiian gallinules to disperse over open ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, Hawaiian Gallinules are thought to be highly sedentary and to maintain territories year-round (Bannor and Kiviat 2002). Despite the sedentary nature of Hawaiian Gallinules, they have colonized wetlands (either unoccupied or created through restoration and management) as numbers increased post-decline (based on genetic data; van Rees et al 2018b), and intraisland dispersal events have been observed (van Rees et al 2018a). Differences in dispersal propensity are postulated to have played a role in how the population decline influenced genetic diversity (Sonsthagen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most wetlands support small numbers of gallinules (five–30 individuals), although two larger wetland complexes may support subpopulations of ∼100 (C van Rees, 2018, unpublished data). To our knowledge, the O‘ahu population of gallinules is an effectively closed system, with no published records of movements between O‘ahu and Kaua‘i ( Banko, 1987 ; van Rees et al, 2018a ), although biannual waterbird surveys show extremely rare occurrences of gallinules on the Big Island, Maui, and Molokai, so the possibility of movement cannot be excluded. Demographic data used for this study were taken from van Rees et al (2018a) , and were collected from fourteen wetland sites on the island from different time periods from 1979–2017.…”
Section: Methodsmentioning
confidence: 96%
“…We generated baseline model parameter values using information on reproduction and survival from van Rees et al (2018a) , with support and supplementation from data on related taxa (e.g., Common moorhen, Gallinula chloropus ; Table 2 ). Even though Hawaiian gallinules do not breed until age 2, there is no evidence of age structure in survival rate beyond year 1 ( van Rees et al, 2018a ). Accordingly, we modeled survival using two age classes: hatch year (hatching to age 1), and after hatch year (age 1+ or adult).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation